2015
DOI: 10.7448/ias.18.1.20022
|View full text |Cite
|
Sign up to set email alerts
|

Tracing defaulters in HIV prevention of mother‐to‐child transmission programmes through community health workers: results from a rural setting in Zimbabwe

Abstract: IntroductionHigh retention in care is paramount to reduce vertical human immunodeficiency virus (HIV) infections in prevention of mother-to-child transmission (PMTCT) programmes but remains low in many sub-Saharan African countries. We aimed to assess the effects of community health worker–based defaulter tracing (CHW-DT) on retention in care and mother-to-child HIV transmission, an innovative approach that has not been evaluated to date.MethodsWe analyzed patient records of 1878 HIV-positive pregnant women an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
9
1
Order By: Relevance
“…Although our study did not have adequate power to detect differences in vertical transmission of HIV, our findings suggest that higher transmission in infants born to DW as compared to RW. Our estimates of HIV transmission among DW were higher than that reported in a study conducted among women who disengaged from care in Zimbabwe, where the observed estimates of 3.6% were reduced to 1.8% following a tracing program which used community workers to ensure that all HIV positive pregnant women were in care throughout the post-partum period [22]. Among the women retained in care, our estimates of vertical transmission are slightly lower than Uganda national estimates of 2.9% [42].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Although our study did not have adequate power to detect differences in vertical transmission of HIV, our findings suggest that higher transmission in infants born to DW as compared to RW. Our estimates of HIV transmission among DW were higher than that reported in a study conducted among women who disengaged from care in Zimbabwe, where the observed estimates of 3.6% were reduced to 1.8% following a tracing program which used community workers to ensure that all HIV positive pregnant women were in care throughout the post-partum period [22]. Among the women retained in care, our estimates of vertical transmission are slightly lower than Uganda national estimates of 2.9% [42].…”
Section: Discussioncontrasting
confidence: 87%
“…Several tracing studies have addressed the outcomes of non-pregnant adults who have become LTFU [18][19][20][21]. However, other than three studies from Zimbabwe, eSwatini and Malawi, there is a dearth of knowledge about the outcomes of pregnant women initiating ART who subsequently become LTFU [22][23][24]. Such outcomes may include estimates of HIV viral suppression, MTCT and care status among women who disengage from HIV care programs.…”
Section: Introductionmentioning
confidence: 99%
“…However, loss of clients along the PMTCT cascade is concerning because it is also a crucial period for ART initiation in HIV-infected infants [27]. Similar trends have been observed in other studies where retention was high during pregnancy but decreased rapidly in the postnatal period [28]. Other studies have reported cumulative retention rates of up to 80% six months postpartum [2729].…”
Section: Discussionmentioning
confidence: 60%
“…Notably, only two papers presented age-disaggregated results [26,27] and one additional paper noted that age did not modify the study results [28]. Among all 37 papers evaluating at least one approach to increase retention, 18 demonstrated no effect on retention [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] and 19 reported a significant effect on retention [26][27][28][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Notably, several papers reported significant improvements in retention at some time points but not at others; these are categorized as reporting a significant effect on retention.…”
Section: Resultsmentioning
confidence: 99%
“…One study was published during 2010 [30], but the remainder were published between 2014 and 2020. Cluster-randomized controlled trials were the most common study design [29,32,[34][35][36][37]39,40,43,47,[56][57][58], and the duration of follow-up across studies ranged from one month [28,30,33,61] to 36 to 60 months' postpartum [38], with two-thirds of studies following women through ≤6 months' postpartum [27,28,30,31,33,[35][36][37][39][40][41][43][44][45]47,48,50,[53][54][55][56][59][60][61][62]. Many studies were restricted to women who were not yet receiving ART when presenting for ANC or delivery, and 12 studies were restricted to women who were aged ≥18 years at enrolment in the study [26,28,29,…”
Section: Resultsmentioning
confidence: 99%